Violence, discrimination, and sexual health practices among adolescent men who have sex with men, transgender women and travestis in three cities in Brazil - Marcelo Ryngelblum; Alexandre Grangeiro; Eliana Miura Zucchi; Marcia Thereza Couto; Ines Dourado; Laio Magno; Unaí Tupinambás; Maria Fernanda Tourinho Peres (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
The HIV epidemic has a disproportionate impact on adolescent and young men who have sex with men (AMSM) and transgender women and travestis (ATGW), with an increased HIV prevalence over the last 10 years. Violence affects the lives of these populations, undermining their ability to self-care and making them more vulnerable to HIV infection. In this study, we aimed to examine the association between different types of victimization by violence and discrimination and sexual health practices of these adolescent populations in steady and casual relationships. We conducted a cross-sectional study using baseline data from the cohort of PrEP1519 project. We used the mean score of sexual health practices as our outcome and the cumulative score of discrimination (within family, community, education, religious, online and public spaces) and violence (physical, sexual and intimate partner) as our exposure variable. We performed linear regression analyses to estimate the association between exposure and outcome. We found that 90% of AMSM and 95% of ATGW experienced at least one form of violence in the three months prior to this study and about 45% of ATGW suffered sexual violence during the same period. Experiencing discrimination within healthcare settings (from facilities or providers) was negatively associated with sexual health practices. Discrimination and violence negatively affect sexual health practices. HIV prevention and care of AMSM and ATGW people should involve listening to their experiences and addressing discrimination and violence in this population.